ANALYZING THE INFLUENCE OF CONSUMER BEHAVIOR ON PURCHASE DECISIONS: EVIDENCE FROM YOUNG PAPUAN ENTREPRENEURS’ CONSUMERS IN JAYAPURA CITY: - - Rut Penina Somisu; Wilhelmina Anastasia Insoraky Arfusau (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2026)
Consumer choices are never as rational as textbooks claim—they are tangled in culture, swayed by peers, and constrained by the price tag. This study investigates the determinants of purchase decisions in the context of young Papuan entrepreneurs in Jayapura City, focusing on the roles of cultural influence, social influence, and price affordability. A quantitative survey was conducted with 174 respondents who had made at least one purchase in recent months, and the data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. Validity was assessed through Pearson correlations, while reliability was confirmed using Cronbach’s Alpha. The results demonstrate that price affordability is the strongest predictor of purchase decisions, while cultural belonging and social trust also exert significant effects. The overall regression model was statistically significant (F = 66.233, p < .001), confirming that consumer behavior is shaped jointly by cultural identity, social dynamics, and economic considerations. These findings advance the understanding of consumer behavior by showing that purchasing is not merely an individual economic act but a collective, context-dependent process rooted in identity, trust, and affordability. The study carries practical and policy implications: entrepreneurs should embed cultural identity and community values in branding and product development, while policymakers can strengthen youth-led ventures through targeted support, subsidies, and digital engagement initiatives to expand market reach.